2018
DOI: 10.1029/2018jc013828
|View full text |Cite
|
Sign up to set email alerts
|

SIDDIES Corridor: A Major East‐West Pathway of Long‐Lived Surface and Subsurface Eddies Crossing the Subtropical South Indian Ocean

Abstract: South Indian Ocean eddies (SIDDIES), originating from a high evaporation region in the eastern Indian Ocean, are investigated by tracking individual eddies from satellite data and co‐located Argo floats. A subsurface‐eddy identification method, based on its steric dynamic height anomaly, is devised to assign Argo profiles to surface eddies (surfSIDDIES) or subsurface eddies (subSIDDIES). These westward‐propagating, long‐lived features (>3 months) prevail over a preferential latitudinal band, forming a permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 72 publications
3
48
0
Order By: Relevance
“…Interaction between these two accumulation regions has already been shown (van Sebille et al, ), but it still needs to be confirmed if this is enough to explain the emptying of the subtropical SIO accumulation region. Second, the drogued simulations show a persistent accumulation forming in a region that is associated with high eddy kinetic energy (Dilmahamod et al, ). It is not yet clear why this accumulation is so stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between these two accumulation regions has already been shown (van Sebille et al, ), but it still needs to be confirmed if this is enough to explain the emptying of the subtropical SIO accumulation region. Second, the drogued simulations show a persistent accumulation forming in a region that is associated with high eddy kinetic energy (Dilmahamod et al, ). It is not yet clear why this accumulation is so stable.…”
Section: Discussionmentioning
confidence: 99%
“…The SICC flows across the entire width of the SIO and splits into three separate branches between the southern tip of Madagascar and the western coast of Australia (Lambert et al, 2016;Menezes et al, 2014). The SICC is also associated with high activity of westward propagating eddies (Dilmahamod et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous results suggested Madagascar cyclonic eddies have the ability to advect mass, heat, and freshwater in distinct depth layers, depending on the ratio between their rotational and propagation speeds. We take the estimates of time‐varying trapping depths for the model April and July eddies and combine them with the temperature and salinity anomalies shown in Figures and through the growth, mature, and decay phases to calculate the available heat and salt contents (AHA, ASA) following (Barceló‐Llull et al, ; Dilmahamod et al, ): AHA=ztrap00Rcρ0CpΘfalse(2πrfalse)drdz, ASA=ztrap00Rcρ0SnormalAfalse(2πrfalse)drdz, where z is the vertical coordinate (depth, m), z trap is the trapping depth (m), ρ 0 is the mean upper ocean density (1,026 kg m −3 ), C p is the specific heat capacity (4,000 J·kg −1 ·°C −1 ), and r is the eddy radius (m). Then temperature and salinity anomalies (Θ ′ and SnormalA, respectively) are calculated comparing model daily fields of the selected dates of study against the corresponding multiyear‐averaged monthly field over the period 1993–2015.…”
Section: Resultsmentioning
confidence: 99%
“…The mean vertically integrated AHA (ASA) of the April eddy was −58.8 × 10 18 ± 65.1 × 10 18 J (−145.5 × 10 10 ± 158.8 × 10 10 kg), and the July eddy was −151.7 × 10 18 ± 83.7 × 10 18 J (−336.7 × 10 10 ± 189.6 × 10 10 kg). We find these averaged estimates of total AHA and ASA (Table ) larger than those found for cyclonic eddies in the Peru‐Chile Current System (−5.9 × 10 18 J and −14.7 × 10 10 kg, respectively; Chaigneau et al ) and in the Western and Eastern Indian Ocean for subsurface cyclonic eddies (−5.1 × 10 18 J and −25.6 × 10 10 kg; Dilmahamod et al ). However, we must also note that estimates in these previous works are based on smoother vertical structures of the eddies since they were constructed from averaging Argo profiles over large areas to provide climatological views.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation